3D Co‐Printing of 3D Electronics with a Dual Light Source Technology (Adv. Mater. Technol. 9/2021). Issue 9 (12th September 2021) - Xiao, Junfeng; Zhang, Dongxing; Guo, Qiuquan; Yang, Jun
Abstract : A Dual‐Light Curing Process A new strategy is presented in article number 2100039 by Jun Yang and coworkers: 3D co‐printing technology to fabricate 3D electronics by collaboratively employing a dual‐light curing process. Here, integrating the metal precursor into the 3D printing material enables the construction of polymeric structures and printing of conductive traces simultaneously, addressing the research challenges in the 3D‐printing electronics using multimatrial deposition process.